Identification of novel target proteins in sebaceous gland carcinoma. Issue 5 (19th June 2012) - Erovic, Boban M.; Al Habeeb, Ayman; Harris, Luke; Goldstein, David P.; Kim, Dae; Ghazarian, Danny; Irish, Jonathan C.
Abstract Background The aim of this study was to identify new target proteins in sebaceous gland carcinoma. Methods A tissue microarray containing 115 core biopsies was constructed and stained for proteins involved in carcinogenesis, angiogenesis, inflammation, and cell‐to‐cell contact. Two investigators independently determined protein expression of all antibodies. Results Vascular endothelial growth factor receptor 2 (VEGFR‐2), platelet‐derived growth factor receptor alpha and beta (PDGFR‐α/‐β), epidermal growth factor receptor (EGFR), cyclooxygenase 1 and 2 (Cox‐1/‐2), myeloid cell leukemia sequence 1 (Mcl‐1), matrix metalloproteinase 1 (MMP‐1), CD9, Bmi‐1, 14‐3‐3σ, glutathione S‐transferase pi (Gstπ), and members of the sonic hedgehog (SHH), AKT, and WNT pathways were significantly overexpressed in sebaceous gland carcinomas. Conclusions We have demonstrated for the first time that proteins related to angiogenesis, inflammation, and cell proliferation are overexpressed in sebaceous gland carcinomas. These proteins may hold promise as novel therapeutic targets for the treatment of sebaceous gland carcinoma. © 2012 Wiley Periodicals, Inc. Head Neck, 2013